2017
DOI: 10.1161/jaha.117.007024
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Exposure Inhibits Angiotensin II–Induced Abdominal Aortic Aneurysm Formation in Mice by Expanding CD4 + Foxp3 + Regulatory T Cells

Abstract: BackgroundPathogenic immune responses are known to play an important role in abdominal aortic aneurysm (AAA) development. Ultraviolet B (UVB) irradiation has been demonstrated to have therapeutic potential not only for cutaneous diseases but also for systemic inflammatory diseases in mice by suppressing immunoinflammatory responses. We investigated the effect of UVB irradiation on experimental AAA.Methods and ResultsWe used an angiotensin II–induced AAA model in apolipoprotein E–deficient mice fed a high‐chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…A well-known positive effect of UVB is immunosuppression. It is shown that UVB-induced immunosuppression is mediated by Treg cells in mouse models of contact hypersensitivity (44,45), experimental autoimmune encephalomyelitis, and atherosclerosis (46,47). UVB therapy is very effective for treatment of skin immunological disorders such as psoriasis and atopic dermatitis (48).…”
Section: Discussionmentioning
confidence: 99%
“…A well-known positive effect of UVB is immunosuppression. It is shown that UVB-induced immunosuppression is mediated by Treg cells in mouse models of contact hypersensitivity (44,45), experimental autoimmune encephalomyelitis, and atherosclerosis (46,47). UVB therapy is very effective for treatment of skin immunological disorders such as psoriasis and atopic dermatitis (48).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of experimental evidence indicates that the dysregulated balance between pro-inflammatory Teffs and anti-inflammatory Tregs contributes to the development and progression of AAA 4,5,11 and atherosclerotic disease 10,16,17 . Recent studies suggest that augmentation of the Treg/Teff ratio, by regulating Teff responses or promoting Treg responses, could be a feasible therapeutic approach for AAA 5,6 as well as atherosclerosis 1820 . Our findings of attenuated Teff immune responses and AAA development mediated by CTLA-4 overexpression does not appear to be due to modulation of Treg responses, because angiotensin II-infused CTLA-4-Tg/ Apoe −/− mice had a markedly reduced number of CD4 + Foxp3 + Tregs compared with angiotensin II-infused Apoe −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies from several independent groups have demonstrated a protective role of forkhead box P3 (Foxp3)-expressing regulatory T cells (Tregs), which play an important role in dominant suppression of excessive immunoinflammatory reactions and maintenance of immune homeostasis 3 , in angiotensin II-induced experimental AAA 4,5 . Tipping the Treg/Teff balance toward Treg function by suppressing Teff responses and promoting Treg responses could be a feasible therapeutic approach for preventing AAA formation 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence demonstrated that increased Th1/IFN- γ , Th17/IL-17, and Th22/IL-22 resulted in elevated blood pressure, and uncontrolled hypertension was one of the main reasons for the presence of AD because higher than normal blood pressure can lead to the apoptosis of vascular SMCs. In recent studies, Hayashi et al reported that the downregulation induced by ultraviolet B irradiation significantly increased the rupture of angiotensin II-mediated aneurysms [ 39 ]. Honjo et al also found that an ApoB-100-related peptide vaccine protects against angiotensin II-induced aortic aneurysm formation and rupture via decreasing Th17/IL-17 expression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%